2020
DOI: 10.12688/f1000research.27287.1
|View full text |Cite
|
Sign up to set email alerts
|

‘The long tail of Covid-19’ - The detection of a prolonged inflammatory response after a SARS-CoV-2 infection in asymptomatic and mildly affected patients

Abstract: ‘Long Covid’, or medical complications associated with post SARS-CoV-2 infection, is a significant post-viral complication that is being more and more commonly reported in patients. Therefore, there is an increasing need to understand the disease mechanisms, identify drug targets and inflammatory processes associated with a SARS-CoV-2 infection. To address this need, we created a targeted mass spectrometry based multiplexed panel of 96 immune response associated proteins. We applied the multiplex assay to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 15 publications
2
77
0
Order By: Relevance
“…Researchers have discovered evidence that patients with persistent symptoms have signs of vessel wall inflammation on imaging 9 and elevated biomarkers consistent with J o u r n a l P r e -p r o o f inflammation. 10 During the SARS-CoV 1 outbreak in 2003, the SARS-CoV 1 virus was detected in myocardial tissue during autopsy providing evidence of direct viral entry into tissues. 11…”
Section: Long-haulersmentioning
confidence: 99%
“…Researchers have discovered evidence that patients with persistent symptoms have signs of vessel wall inflammation on imaging 9 and elevated biomarkers consistent with J o u r n a l P r e -p r o o f inflammation. 10 During the SARS-CoV 1 outbreak in 2003, the SARS-CoV 1 virus was detected in myocardial tissue during autopsy providing evidence of direct viral entry into tissues. 11…”
Section: Long-haulersmentioning
confidence: 99%
“…However, given the many unanswered questions regarding the nature of the virus-host interactions in COVID-19, additional well-designed and well-controlled studies will be needed. This will be particularly important as more attention turns towards elucidating the pulmonary and extrapulmonary pathologies in patients suffering from post-acute sequelae of SARS-CoV-2 infection (PASC) or long COVID ( 45 ). For autopsy pathologists, it is important to remember that observations made at autopsy on patients who died from acute or subacute SARS-CoV-2 infection may not be readily applicable to those patients who recover from their illness.…”
mentioning
confidence: 99%
“…Most studies refer to their patient recruitment in terms of recovery (e.g., "COVID-19 survivors" 56 or "discharged COVID-19 patients" 57 ) or clinical course (e.g., "medium-and long-term consequences" 58 or "delayed return to usual health" 59 ). A number of studies did refer to their participant groups using terms like "Long COVID", 13,[60][61][62][63][64][65][66][67][68] "post-acute COVID-19", 69,70 "post-COVID syndrome", 71 or "post-acute COVID-19 syndrome", 72 but these terms were not standardized among studies. A few studies 46,60 acknowledged the proposed distinction at 12 weeks post-infection between post-acute COVID-19 and chronic COVID-19, 37 but otherwise the definitions used typically did not refer to any proposed operationalizations of Long COVID.…”
Section: Literature Reviewmentioning
confidence: 99%
“…46 In the latter case, these patients could fall under either the Long COVID (PACS) or chronic COVID-19 definitions if using a 12-week cutoff. 37,44 Because the relationship between infection, symptoms, and viral clearance occupies a wide distribution, 62,90,91 this heterogeneity among and sometimes within studies could introduce significant variability in disease course within and among patient cohorts. Finally, studies varied wide in the terminology used to describe patient-reported symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%